СТРАТЕГИИ ПРИВЛЕЧЕНИЯ ПРЯМЫХ ИНОСТРАННЫХ ИНВЕСТИЦИЙ (ПИИ) ДЛЯ ИННОВАЦИОННОГО РАЗВИТИЯ СТРАНЫ НА СОВРЕМЕННОМ ЭТАПЕ - Раимова Сабина Икром кизи; Шарипова Умидахон Адхамовна (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This article examines the successful model of Malaysia’s economic transformation from a commodity-dependent exporter to a modern,innovation-driven industrial nation. The study analyzes historical stages of development, structural changes, and strategic priorities that have enabled Malaysia to integrate deeply into global value chains. Special attention is paid to the state’s role in building a national innovation ecosystem and how this focus on high technology has shaped the country’s export structure and competitiveness. The prospects for innovative cooperation between Malaysia and the Republic of Uzbekistan are also explored.